Напрями розвитку внутрішнього туризму в Україні - Марценюк, Лариса Володимирівна; Нєцвєтов, Андрій (Дніпропетровський державний університет внутрішних справ, Дніпро, 2023)
UKR: Окреслено основні перспективні види туризму, котрі можна розвинути в Україні у післявоєнний період, зважаючи на стратегію сталого розвитку суспільства в цілому та в Україні зокрема. Зосереджено увагу на розвитку велотуризму, водного та духовного видів туризму. Надано короткий перелік туристичних локацій у Дніпропетровській області, що визнані «туристичними магнітами».

ENG: The main promising types of tourism that can be developed in Ukraine in the post-war period are outlined, taking into account the strategy of sustainable development of society in general and Ukraine in particular. The authors focused attention on the development of bicycle tourism, water and spiritual types of tourism. A short list of tourist locations in the Dnipropetrovsk region that are recognized as "tourist magnets" is provided. After the coronavirus pandemic, most countries took a course to develop domestic tourism. Ukraine was not an exception in this matter. All program documents outlining the directions of tourism development in Ukraine emphasize the development of domestic tourism. It is domestic tourism that will allow Ukrainians to travel within their country, get to know its culture, and attract foreign tourists to visit tourist locations in our country. This will increase the number of jobs and attract revenues to budgets of various levels. It is clear that for any tourist in the first place when choosing a trip, safety comes first, and then all other factors are added, for example, the cost of the tour, duration, special conditions, etc. As long as the war continues in Ukraine, there are no stable prerequisites for the development of tourism, because the gathering of people in one place can be dangerous due to Russian aggression. At the same time, Ukraine has post-war plans for the reconstruction of the country as a whole. This will apply not only to critical infrastructure facilities, but also to transport and tourist infrastructure. Of course, all hotels, restaurants, parks will be restored and new, even better ones will be built. In this study, we singled out only a few types of tourism, the development of which is appropriate after the war, namely: water tourism, bicycle tourism, spiritual tourism, but at the same time, we must admit that there are other, potentially popular types of tourism in Ukraine in the future: railway, military, greyhound, recreational, extreme, business, cognitive, educational, medical, aviation, scientific, research, adventure, religious, virtual, in houses on wheels, etc. Also, we focused our attention on only six tourist magnets of the Dnipropetrovsk region, but there is no doubt that there are many other interesting things to visit in this region. Other regions of Ukraine also have their own tourist locations and they will definitely enter the world rankings of tourist visits in the post-war period. When planning trips, it is recommended to choose conscious tourism, that is, to choose such recreation destinations, during which they will not harm nature or the environment as a whole.
Domestic Tourism Development Directions in Ukraine
Л. Марценюк: ORCID 0000-0003-4121-8826
Keywords: туризм; внутрішній туризм; велотуризм; водний туризм; духовний туризм; tourism; domestic tourism; bicycle tourism; water tourism; spiritual tourism; КЕМ; TECHNOLOGY